PENGARUH PERSEPSI IMPLEMENTASI MANAJEMEN SEKOLAH DAN KOMPETENSI MANAJERIAL TERHADAP EFEKTIVITAS KINERJA TENAGA KEPENDIDIKAN PADA SMP NEGERI DI KECAMATAN BANGKO PUSAKO KABUPATEN ROKAN HILIR - Ilyas Ilyas; Hasnah Faizah AR; Daviq Chairilsyah (Jurnal JUMPED (Jurnal Manajemen Pendidikan), 2017)
The objective of study were to determine the influences of perception schoolmanagement implementation on educational personnel performance at state junior high schoolin Kecamatan Bangko Pusako Kabupatek Rokan Hilir, to determine the influences of managerialcompetence effectiveness on educational personnel performance at state junior high school inKecamatan Bangko Pusako Kabupatek Rokan Hilir, and to determine the influences of perceptionschool management implementation and managerial competence effectiveness on educationalpersonnel performance at state junior high school in Kecamatan Bangko Pusako KabupatenRokan Hilir. The research was conducted in all Junior High School in District Bangko PusakoRokan Hilir Riau .. Samples taken as many as 80 people. The instrument used to collect datafor all variables by using a questionnaire. Validity was tested by using Pearson product momentformula. Instrument reliability coefficient calculated by using Cronbach alpha. Research resultsshowed positive influence between performance management practices in schools witheducational personnel. Partially, school management practices affect the 73.4% value ofperformance educational personnel at Junior High School in District Bangko Pusako RokanHilir. There is a positive influence between managerial competence effectiveness with educationpersonnel performance. Partially, managerial competence effectiveness affecting 82.2% ofthe performance value of education personnel at Junior High School in District Bangko PusakoRokan Hilir. There is a positive influence between the implementation of school managementand managerial competence effectiveness together with the educational personnel performance.Implementation of school management and managerial competence effectiveness together affect83.9% Performance value educational personnel at Junior High School in District BangkoPusako Rokan Hilir.